Synthesis and characterization of carboxymethyl cellulose powder and films from Mimosa pigra - Rachtanapun P. (2014)
Mimosa pigra peel was sun-dried for 2 days and then ground before being boiled with 30%w/v sodium hydroxide (NaOH) at 100°C for 3 h, washed and then dried at 55°C to constant weight. The cellulose was then synthesized using different NaOH concentrations and monochloroacetic acid (MCA) in isopropyl alcohol (IPA). Effects of various NaOH concentrations on degree of substitution (DS), viscosity and thermal of carboxymethyl cellulose from Mimosa pigra peel (CMCm) were investigated. The increasing of NaOH concentration resulted in increasing DS and viscosity. However, viscosity of CMCm decreased as temperature increased. Thermal properties were studied using differential scanning calorimetry (DSC). The melting point of the samples decreased as %NaOH increased. The effects of various NaOH concentrations in CMCm synthesis on the mechanical properties and water vapor permeability (WVP) of the CMCm films were investigated as well. With increasing NaOH concentrations (30-50%) were also found to result in improved mechanical properties. However, when the level of NaOH concentration was 60%, the mechanical properties of the CMC films decreased. This result indicates that the highest mechanical properties were found for 50% NaOH-synthesized CMC m films. The WVP of the CMCm films increased as %NaOH increased. In addition, the CMCm films were tested to determine the effect of glycerol as a plasticizer on the mechanical properties. Increasing the amount of glycerol showed an increase in elongation at break but also led to a decrease in tensile strength. Copyright © 2010 Wiley Periodicals, Inc.